EMIRATE OF BUKHARA - Jo`ramurodov Islombek Gulshanbek o`g`li; Shavqatulloyev Do`stmuhammad; Ergashev Odilbek (Journals Park Publishing, 2022)
The Emirate of Bukhara (Persian: امارت بخارا,, romanized: Amārat-e Bokhārā, Chagatay: بخارا امرلیگی, romanized: Bukhārā Amirligi) was the last emirate of the Mangit dynasty of Uzbeks[8] that existed from 1785 to 1920 in what is now modern-day Uzbekistan, Tajikistan, Turkmenistan and Kazakhstan. It occupied the land between the Amu Darya and Syr Darya rivers, known formerly as Transoxiana. Its core territory was the land along the lower Zarafshan River, and its urban centres were the ancient cities of Samarqand and the emirate's capital, Bukhara. It was contemporaneous with the Khanate of Khiva to the west, in Khwarazm, and the Khanate of Kokand to the east, in Fergana. In 1920, it ended with the establishment of the Bukharan People's Soviet Republic.
Keywords: Islamic sharia; separatist; Movarounnahr